Equivalence of K-Functionals and Modulus of Smoothness Generated by The q -Rubin Operator - Rebhi, Sami (Sarajevo Journal of Mathematics, 2022)
In this paper, the equivalence between K-functionals and modulus of smoothness tied to a q -Rubin operator was studied.